Safety And Health Management At Construction Site Of Building Projects - Nurdin, Muhammad Ezam (Universiti Sains Malaysia, 2022)
Regulations and practices related to safety and health are meant to avoid accidents or injuries in workplaces or public spaces. It has to do with protecting workers' safety and the health of everyone that could be harmed by their job. All organisations, including those in the construction sector, should adhere to appropriate safety and health practices to reduce workplace accidents. The construction industry significantly impacts the economic and social climate of the nation. The personnel at the site need a safer working environment for their physical and emotional health. Implementing safety and health measures at a building site positively impacts employees' wellbeing, productivity, and project success. But there are still certain aspects of appropriate safety level execution at construction sites are lacking in our nation's buildings. The data has shown shortcomings in the current building project safety and health standards that will need to be fixed over time. The purpose of this study is to evaluate the implementation of safety and health at building construction sites from various perspectives. The survey's findings indicate that the part of safety culture most strongly connected with stakeholders' perception is the forced culture that requires a safe working environment to eliminate the risk of accidents or injuries. Additionally, the safety toolbox training aspect, which is completed before work begins, is the one that is most often practised in actual situations. The central determining factor in implementing safety and health in construction is compliance with OSH regulations from a technological perspective. It is anticipated that this study will provide views and suggestions to the stakeholders in the construction industry so they can understand how implementing safety and health measures might benefit building projects while safeguarding the health and safety of those employed in this industry.